Configuration of Magnetotail Current Sheet Prior to Magnetic Reconnection Onset. Issue 6 (25th March 2022) - An, Xin; Artemyev, Anton; Angelopoulos, Vassilis; Runov, Andrei; Lu, San; Pritchett, Philip
Abstract: The magnetotail current sheet configuration determines magnetic reconnection properties that control the substorm onset, one of the most energetic phenomena in the Earth's magnetosphere. The quiet‐time current sheet is often approximated as a two‐dimensional (2D) magnetic field configuration balanced by isotropic plasma pressure gradients. However, reconnection onset is preceded by the current sheet thinning and the formation of a nearly one‐dimensional (1D) magnetic field configuration. In this study, using particle‐in‐cell simulations, we investigate the force balance of such thin current sheets when they are driven by plasma inflow. We demonstrate that the magnetic field configuration transitions from 2D to 1D thanks to the formation of plasma pressure nongyrotropy and reveal its origin in the nongyrotropic terms of the ion distributions. We show that substorm onset may be controlled by the instability and dynamics of such nongyrotropic current sheets, having properties much different from the most commonly investigated 2D isotropic configuration. Plain Language Summary: The geomagnetic field lines are stretched by the solar wind into an elongated magnetotail behind the Earth, a region supported by strong equatorial sheet‐like plasma currents. The stability of the magnetotail current sheet configuration controls the substorm onset, one of the most powerful phenomena in the Earth's magnetosphere. The most commonly investigated current sheet models based on the isotropic stress balance have difficulties in describing the most intense thin current sheets. Using computer simulations, we find that thinning of the magnetotail current sheet creates a quasi‐1D equilibrium accompanied by ion pressure nongyrotropy. Therefore, substorm onset may be controlled by the instability and dynamics of such nongyrotropic current sheets, having properties much different from the most commonly investigated 2D isotropic configuration. Key Points: Nongyrotropic pressure gradients alter significantly the configuration of thin magnetotail current sheets before reconnection onset Ion pressure nongyrotropy is caused by velocity shear of off‐equatorial ion outflow during current sheet thinning Nongyrotropic pressure may be critical to the formation and stability of thin current sheets in the magnetotail